COMPARATIVE STUDY OF PRODUCTION PERFORMANCE AMONG LOCAL QUAILS - Chatoo, Kurdo B.; Al-Barzinji, Yousif M.S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was carried out to compare the productivity performance of three lines of local quail. The results showed a significant superiority in the daily gain weight (3.76 g/day/quail) and marketing weight (167.2 g/quail) for brown quail over other colors. Also, significant differences were found in the dressing ratio between males (67.8%) and females (65.76%). As for the egg production of quail, it was found a significant superiority of the desert quail over the other colors in the number of eggs produced, the average egg weight (9.73 g/ egg) and the HDEP (78.6 %) with the best feed conversation (2.15 g / g of egg). The results also show that the white-colored quail was average between the other two colors for the characteristics of the productive performance of body weight and egg production. It could be concluding from these results the possibility of directing the different colors of a particular trait and developing it into specialized lines for the production of eggs or meat through the selection process.